A world of homeowners : American power and the politics of housing aid - Kwak, Nancy, 1973- (Historical studies of urban America., 2015)
Is there anything more American than the ideal of homeownership? In this groundbreaking work of transnational history, Nancy H. Kwak reveals how the concept of homeownership became one of America's major exports and defining characteristics around the world.